A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, Pilar (2022)
Performance-ritual as a form of unconventional action, spontaneous and immediately directed to an audience inserted in a given scientific, artistic, or cultural event, has been adopted as a vehicle for artistic intervention and social criticism taking the university as the platform for creativity, freedom, and questioning of the normal-hegemonic and power structures.In this article, we approach five performative interventions carried out between the years 2008 and 2010, in the path of the so-called “academic performance,” which took place in Japan, Spain, Portugal, and Cape Verde, where the ritualism and the dynamics of power were reflected and questioned, their meaning and exercise, in the university space, as well as the gradual hegemony of the university reform project known as the Bologna model.In the article, we analyze each of these performances from the symbolic, iconographic, pointing to the space of post-digital creation.